Pengaruh Disiplin Belajar, Konformitas Teman Sebaya, Kepercayaan Diri, Lingkungan Belajar dan Tekanan Orangtua Terhadap Perilaku Menyontek Siswa Kelas VIII SMP Negeri 25 Padang - Yola Afrianti; Desi Areva; Putri Meliza Sari (STKIP PGRI Sumatera Barat, 2023)
This study aims to analyze: 1) the influence of learning discipline on cheating behavior, 2) the effect of self-confidence on cheating behavior, 3) the influence of peer co-operation on cheating behavior, 4) the influence of the learning environment on cheating behavior, 5), the influence of parental pressure on cheating behavior. cheating behavior, 6) the influence of learning discipline, peer conformity, self-confidence, learning environment and parental pressure together influence cheating behavior. The results of this study indicate that: Learning discipline has a significant effect on cheating behavior in class VIII SMP Negeri 25 Padang. Peer conformity has a significant effect on cheating behavior in class VIII SMP Negeri 25 Padang. Self-confidence has a significant effect on cheating behavior in class VIII SMP Negeri 25 Padang. The learning environment has a significant effect on the cheating behavior of class VIII students of SMP Negeri 25 Padang. Parental pressure on cheating behavior of class VIII students of SMP Negeri 25 Padang.